2021
DOI: 10.3390/jcm10112339
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Plasma Amino Acid and Anthropometric Profiles with Brown Adipose Tissue Density in Humans

Abstract: This study examined the relationship between plasma amino acid (AA) concentrations, including branched-chain AAs, and brown adipose tissue density (BAT-d). One hundred and seventy-three subjects (69 men, 104 women) aged 22–68 years were recruited during the winter season. AAs were comprehensively quantified using liquid chromatography-time-of-flight-mass spectrometry. The total hemoglobin concentration in the supraclavicular region ([total-Hb]sup), an indicator of BAT-d, was assessed using near-infrared time-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Yasuoka et al conducted CE-TOFMS-based metabolomics of saliva samples collected from patients with head and neck cancers who underwent chemotherapy [4]. Kuroiwa et al analyzed amino acids in human plasma samples and found that branched-chain amino acid concentrations correlated with brown adipose tissue density [5].…”
mentioning
confidence: 99%
“…Yasuoka et al conducted CE-TOFMS-based metabolomics of saliva samples collected from patients with head and neck cancers who underwent chemotherapy [4]. Kuroiwa et al analyzed amino acids in human plasma samples and found that branched-chain amino acid concentrations correlated with brown adipose tissue density [5].…”
mentioning
confidence: 99%